2007
DOI: 10.1111/j.1365-2923.2007.02802.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and types predict medical school stress: a six-year longitudinal and nationwide study

Abstract: This is the first study to show that a specific combination of personality traits can predict medical school stress. The combination of high neuroticism and high conscientiousness is considered to be particularly high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
120
3
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(145 citation statements)
references
References 29 publications
14
120
3
8
Order By: Relevance
“…The positive impact of conscientiousness on academic achievement was confirmed in several studies conducted in the medical context (Chamberlain, Catano, & Cunningham, 2005;Ferguson, James, O'Hehir, & Sanders, 2003;lievens, Ones, & Dilchert, 2009;Tyssen et al, 2007). Especially the facets self-discipline (e.g.…”
Section: Personality Characteristics As Predictors Of Academic Achievmentioning
confidence: 60%
“…The positive impact of conscientiousness on academic achievement was confirmed in several studies conducted in the medical context (Chamberlain, Catano, & Cunningham, 2005;Ferguson, James, O'Hehir, & Sanders, 2003;lievens, Ones, & Dilchert, 2009;Tyssen et al, 2007). Especially the facets self-discipline (e.g.…”
Section: Personality Characteristics As Predictors Of Academic Achievmentioning
confidence: 60%
“…Also, research findings suggest that sociability, a prominent feature of the Extraversion factor, is an important mediating variable in the clinical performance of medical students (Ferguson et al 2003;McManus et al 2004;Hojat et al 2004a;Knights & Kennedy 2007;Tyssen et al 2007;Lievens et al 2009). However, their results on the Extraversion factor are less consistent in the preclinical than clinical phases of medical education (Piedmont et al 1991;Lievens et al 2002).…”
Section: Selected Personality Instruments Frequently Used In Medical mentioning
confidence: 99%
“…Even in a Scandinavian country with reasonably equitable working conditions across the genders, women still experience a greater total workload because they incur greater domestic responsibilities than men 24) . We also expect that personality traits may be important 25,26) , and have recently found that both neuroticism and conscientiousness may predict stress at medical school level 27) , and that neuroticism is a major predictor of general work stress during internship 28) . However, we have not studied stress beyond internship or controlled for other possible stress factors, such as the number of children and total working hours per week in a repeated measures predictor model.…”
Section: Introductionmentioning
confidence: 99%